2023
DOI: 10.1088/1572-9494/acf305
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium kinetics effects in Richtmyer–Meshkov instability and reshock processes

Yiming Shan,
Aiguo Xu,
Lifeng Wang
et al.

Abstract: Kinetic effects in the inertial confinement fusion ignition process are far from clear. In this work, we study the Richtmyer-Meshkov instability (RMI) and reshock processes by using a two-fluid discrete Boltzmann method (DBM). The work begins from interpreting the experiment conducted by Collins and Jacobs [J. Fluid Mech. 464,113-136(2002)]. It shows that the shock wave causes substances in close proximity to the substance interface to deviate more significantly from their thermodynamic equilibrium state. The Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…In particular, numerical simulation has promoted relative research due to its convenience and efficiency, and it can enrich our understanding of the RM instability from multiple perspectives. These perspectives are mainly attributed to the following three levels: macroscopic [18][19][20][21][22][23][24], microscopic [25,26], and mesoscopic aspects [27][28][29]. In the macroscopic view, various codes based on hydrodynamic governing equations, such as Euler or Navier-Stokes equations, have been widely used to simulate fluid instability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, numerical simulation has promoted relative research due to its convenience and efficiency, and it can enrich our understanding of the RM instability from multiple perspectives. These perspectives are mainly attributed to the following three levels: macroscopic [18][19][20][21][22][23][24], microscopic [25,26], and mesoscopic aspects [27][28][29]. In the macroscopic view, various codes based on hydrodynamic governing equations, such as Euler or Navier-Stokes equations, have been widely used to simulate fluid instability.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Chen et al [28] used the multiple-relaxation-time DBM to investigate the non-equilibrium characteristics of a coexistence system involving both RM and Rayleigh-Taylor instability and found that the non-equilibrium effect of the system increases as the Mach number increases, while the effect of gravity acceleration on the non-equilibrium characteristics is different at various phases. In 2023, Shan et al [29] employed the two-fluid DBM to investigate the non-equilibrium kinetic effects on the RM instability and reshock process and found that lighter fluid has a higher entropy production rate than heavier fluid. Moreover, the DBM also provides new insights for complex fluid systems, such as hydrodynamic instability [39][40][41][42][43], multiphase flow [44,45], reactive flow [46], etc.…”
Section: Introductionmentioning
confidence: 99%